The Effects of Projects Based Chemistry Learning Model, Assisted by Chemsong Video to Students’s Learning Completeness and Creativity - Fourniyati, Indang Retno; Nuswowati, Murbangun; Cahyono, Edy (Journal of Innovative Science Education, 2020)
This study aims to examine the effect of project-based chemistry learning models on cearning completeness and student creativity through the Chemsong video making project. The research method uses the pretest-posttest control group design while the data analysis uses the parametric statistical test that is N-gain, the independent sample t test and the sample t-test paired test. The sample in this study was obtained by cluster random sampling technique from the population of all students of SMK N 8. The gain normality test showed that the average results of the pretest-posttest clasical learning completeness increased by 0.53 with the criteria being in the experimental class and the control class at 0,31 with moderate criteria. The results of the independent sample t-test showed that there was a significant difference in the classical learning completeness of the experimental and control group students, which was 4.56 greater than t critic 1.98 with a significance level of 5%. In the paired sample t test, the value of sig. (2-tailed) of 0,000 <0.05. Whereas the results of student creativity t-test obtained sig values. (2-tailed) of 0,000 <0.05. So it can be concluded that the application of the chemistry learning model based on the Chemsong video project has an effect on improving student mastery learning and creativity.